Seguimiento de pacientes con VIH durante la pandemia de la Covid-19 en la región de Callao, Perú - Vasquez-Velasquez, Cinthya (2024)
The diagnosis of human immunodeficiency virus (HIV) is key for the initiation of antiretroviral therapy (ART). Viral load (VL) values and other immunological components are essential for the follow-up and prognosis of people with HIV. The aim of the study was to evaluate patients with a confirmatory diagnosis of HIV residing in the Callao region. Prospective study, in which 289 adult residents of the Callao region were evaluated, confirmatory and post ART treatment measurements were performed. For the difference of means, Student’s T-test for paired samples was calculated, considering p<0.05 as statistical significant.  People who received ART showed a significant decrease in VL values and an increase in CD4+. There have been a successful disease management and control of the HIV-infected population in Callao.